Respuesta :
Answer:
SOMEONE HURRY AND ANSWER THIS
Step-by-step explanation:
Convert -6/7 to 7/6 because they have to multiply together to equal -1.
Plug the -3 into x and the -5 into y
-5=7/6(-3)+b
(y=mx+b format)
-5=-3.5+b
Add 3.5 to both sides.
-1.5=b
Now add to the equation we had at the top to get your answer.
y=7/6x-1.5
Plug the -3 into x and the -5 into y
-5=7/6(-3)+b
(y=mx+b format)
-5=-3.5+b
Add 3.5 to both sides.
-1.5=b
Now add to the equation we had at the top to get your answer.
y=7/6x-1.5